Peran Orang Tua dalam Menanamkan Nilai Sopan Santun pada Anak Usia 5-6 Tahun di Rumah Betang So Langke - Fransiska, Fransiska; Sudarto, Sudarto; Paria’ang, Kristiana (Absorbent Mind, 2024)
Every parent has a role in instilling the values of good manners in their children, as well as the parents who live in Rumah Betang So Langke who apply the values of good manners based on the life of the Dayak Tribe. The aim of this research is to describe the role of parents in instilling good manners in children aged 5-6 years at Rumah Betang So Langke. The research method used was qualitative in the form of a case study with a total of 11 resource persons consisting of parents, children, and traditional leaders. The results of the study show that: 1) The role of parents in instilling good manners in children aged 5-6 years at the Rumah Betang So Langke is by providing motivation, educating, and guiding, as well as by providing examples and role models for children. 2) The polite values applied by parents to children aged 5-6 years at Rumah Betang So Langke are greeting and kissing hands, saying please, saying hello when entering, asking without forcing, apologizing, calling people by good names, respecting others, speaking, fart, and respecting those who worship. Factors that influence parents in instilling good manners in children aged 5-6 years at Rumah Betang So Langke are parental factors and environmental factors.